2021
DOI: 10.1111/anae.15500
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Australian/New Zealand organisational position statement on extended‐release opioid prescribing among surgical inpatients: a dual centre before‐and‐after study

Abstract: Summary Extended‐release opioids are often prescribed to manage postoperative pain despite being difficult to titrate to analgesic requirements and their association with long‐term opioid use. An Australian/New Zealand organisational position statement released in March 2018 recommended avoiding extended‐release opioid prescribing for acute pain. This study aimed to evaluate the impact of this organisational position statement on extended‐release opioid prescribing among surgical inpatients. Secondary objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…49 Multiple studies demonstrate that the addition of SR opioids does nothing to improve analgesia but rather can contribute to harm because the overall total opioid dose increases with a predictable attendant increase in adverse events. 50…”
Section: How Do We Implement the Most Modifiable Points In The Recent...mentioning
confidence: 99%
See 2 more Smart Citations
“…49 Multiple studies demonstrate that the addition of SR opioids does nothing to improve analgesia but rather can contribute to harm because the overall total opioid dose increases with a predictable attendant increase in adverse events. 50…”
Section: How Do We Implement the Most Modifiable Points In The Recent...mentioning
confidence: 99%
“…While this may be regarded as a draconian method to thwart the right of physicians to prescribe as they see fit, there has been a substantial lead time of physician education around this issue. The release of the ANZCA/FPM statement initiated and facilitated debate, which has been reflected in substantial changes to prescribing behaviour in hospitals, 50 while GP prescribing appears to be decreasing in metropolitan areas (Liu et al., submitted to Anaesthesia and Intensive Care ).…”
Section: Hospital Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, welcome to read the paper by Awadalla et al. [12] published in this issue of Anaesthesia , in which they have sought to determine whether the publication of the ANZCA/FPM position statement [4] had an impact on the prescription of extended‐release opioids after surgery across two hospital systems in Sydney. The two hospitals did not alter their guidance and there were no academic detailing or audit and feedback activities as in the other opioid safety initiatives [13].…”
mentioning
confidence: 99%
“…While Awadalla et al [12] have demonstrated the impact of the ANZCA and its FPM position statement [4]…”
mentioning
confidence: 99%